(untitled) (World of finance, 2021)
Introduction. The ownership encompasses the subject’s ownership of a tangible or intangible object with all the formalized or informal manifestations of the phenomenon. Therefore in the process of property taxation it is necessary to take into account all the features of ownership, to consider this process from the standpoint of imposing tax on the owner in inseparable relationship with its property, social characteristics and impact on economic interests. The purpose of the article is to scientifically substantiate the essence and determine the criteria of the phenomenological approach to the property taxation. Results. The essence of the category “property” in the reference literature is investigated, its key features are substantiated, on the basis of which the own vision of the essence of this definition is presented. The concept of “property taxation” is defined from the standpoint of taking into account the characteristics of the category “property”. Criteria for the implementation of the phenomenological approach to property taxation are proposed. Ways to minimize tax liabilities in the process of property taxation are covered. Conclusions. The concept of “property taxation”, taking into account its features and in accordance with the content of the taxation process, we have defined as the imposition of taxes on entities in the process of possession of tangible or intangible goods, acquisition of property rights and its termination.